Recommendations for the ethical conduct of vaccination awareness campaigns by biopharmaceutical companies - Claar van der Zee; Veronique Delpire; Volker Vetter; Tatjana Poplazarova (Taylor & Francis Group, 2022)
Health awareness campaigns educate and inform the public about particular health conditions with the aim of either changing behavior or enhancing uptake of appropriate healthcare, such as vaccination or screening. The campaigns may be run by governments and public health bodies but are also deployed by biopharmaceutical companies. Industry-sponsored disease awareness (DA) campaigns intend to provide information about diseases and their prevention or treatment, without mentioning specific products. In most countries, DA campaigns fall outside of the laws and regulations that apply to promotion of medicines. Currently, guidance for industry is limited and only exists at national level. This article provides an overview of existing guidance on DA campaigns, discusses benefits and risks, and proposes recommendations for industry-sponsored vaccination awareness campaigns.